Managerial roles and functions in negotiation process - W. Kozina, Andrzej (Business, Management and Economics Engineering, 2014)
The paper is focused on negotiation processes performed in a company and presents author’s concept of the description of the roles and functions accomplished by managers within those processes and being of significant importance from the point of view of negotiations’ outcomes. Such a concept aims at providing the analysis and conducting of business negotiations with effective support. Firstly (following introduction), the concept, types, and comprehensive model of such negotiations is presented as a useful methodological framework for specifying managerial roles and functions. Secondly, some classic concepts of those roles are reviewed, drawing special attention to the ones that concern negotiation process. Thirdly, general managerial functions within that process are described. Fourthly, those functions are precised by relating them to typical hierarchical levels. Fifthly, peculiar managerial functions within negotiating team are discussed. Finally, specific issue of the role of manager as a mediator is addressed. Summing up the paper, the crucial areas for subsequent research were pointed out. In order to elaborate the presented concept the author carried out the comparative study of negotiation literature as well as developed his original ideas.